Ironía y descentramiento en los Artefactos de Nicanor Parra y Guillermo Tejeda (2014)
This essay will develop the diverse plurality of the ideas behind the Artefactos in relation to in the images created by Guillermo Tejera. It will try to point out the necessity of studying them together as a whole. Nicanor Parra uses an ironic distance from his self to exhibit a wide and diverse range of ideas that find a field to develop within the images that go with them. The images allow new meanings to open and subvert the regular course of the poetic discourse. To exemplify this subject, this essay will use primarily the Chilean poet’s irreverence towards left and right wing politics during the seventies.